Russia’s Foreign Trade with the GCC Countries: Dynamics, Characteristics and Opportunities - L. V. Shkvarya (Vestnik MGIMO-Universiteta, 2023)
This article examines the foreign trade relations between the Russian Federation and the states of the Cooperation Council of the Arab States of the Persian Gulf (GCC) in the 21st century. It considers the development of bilateral trade and economic cooperation with Middle Eastern states, particularly the Arabian monarchies, as an essential direction for enhancing Russia's integration into the global economic system in the context of increasing anti-Russian sanctions. The study's relevance lies in the Russian Federation's need to intensify foreign trade and investment cooperation with friendly states under the current circumstances. The research holds theoretical and practical significance for understanding the characteristics, challenges, and future development of bilateral trade relations with Gulf states.The article aims to analyze the current state of mutual trade between the Russian Federation and GCC countries from 2000 to 2021 and identify the main factors influencing the dynamics and effectiveness of this trade. It establishes that trade and economic cooperation between both sides are founded on a stable objective basis, characterized by similarities and proximity in economic potential levels between the Russian Federation and the GCC countries as a collective business entity, considering individual country characteristics. The economic foundations and mutual benefits remain a priority for further cooperation. Trade volumes, both in goods and services, have shown steady growth, particularly in the past 5-6 years, although there are significant differentiations among countries. The United Arab Emirates (UAE) remains Russia's primary trading partner within the GCC. However, trade flows between Russia and the UAE, as well as other Gulf states, are imbalanced, with Russian exports to the Arabian monarchies significantly exceeding imports from the region. The commodity structure of bilateral trade also requires improvement, offering opportunities for both parties to enhance efficiency. The author suggests that future efforts should focus on developing trade in areas that contribute to economic diversification, the establishment of foundations for "green energy" and other promising sectors, and continuous enhancement of the regulatory framework for cooperation.The analysis draws on data from the UNCTAD international database, ensuring the formulation of reliable and well-founded conclusions. The research utilizes various methods, including comparative analysis, statistical analysis, factor analysis, as well as historical, institutional, and causal approaches.